2014
DOI: 10.1515/hf-2013-0167
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of sodium lignosulfonate above a critical temperature

Abstract: Single molecules of sodium lignosulfonate (NaLS) were prepared and their aggregation behavior was studied as a function of temperature. The molecular dispersity of the NaLS solutions were confirmed by dynamic light scattering (DLS), and the aggregation behavior was studied by DLS and static light scattering (SLS), fluorescence spectrometry (FS), and atomic force microscopy (AFM). It was demonstrated that NaLS molecules started to aggregate above a critical temperature and the aggregation behavior was related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Because of their spherical structure, LSs tend to lose their charge at about 40°C in 0.1 mol l -1 NaCl (Kontturi et al 1992). Our experiments also proved that LSs have a minimum Zeta potential at about 38°C (Qian et al 2013b). Vainio et al (2008) suggested an oblate spheroid shape of LSs in solutions.…”
Section: A Modified Microgel Modelsupporting
confidence: 68%
See 1 more Smart Citation
“…Because of their spherical structure, LSs tend to lose their charge at about 40°C in 0.1 mol l -1 NaCl (Kontturi et al 1992). Our experiments also proved that LSs have a minimum Zeta potential at about 38°C (Qian et al 2013b). Vainio et al (2008) suggested an oblate spheroid shape of LSs in solutions.…”
Section: A Modified Microgel Modelsupporting
confidence: 68%
“…If aqueous solutions of sodium lignosulfonate (NaLS) are investigated by dynamic light scattering (LS dyn ), a fast mode and a slow mode dispersion can be differentiated (Qian et al 2013a). The former is attributed to the presence of single NaLS molecules, and the latter to NaLS aggregates, which are large temporal molecular associations with Coulomb interactions as the active force (Qian et al 2013b). Actually, LSs are never completely dissolved as molecular disperse solutions in water.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the geometrical representation for individual lignosulfonate molecules used by Vainio et al [85], i.e., flat cuboid-like particles, is not consistent with the spheroidal conformation reported by other authors [4,21,115]. Lignosulfonate aggregation can be induced by increasing lignosulfonate or salt concentration, by adding alcohol, by reducing pH, and by increasing the temperature [82,85,123]. A common denominator among most of these actions is that electrostatic repulsion is reduced, which may further enhance hydrophobic interactions.…”
Section: Self-association and Agglomeration In Aqueous Solutionmentioning
confidence: 87%
“…Lignosulfonate aggregation was also reported to be caused by a temperature increase to 38 °C and above [123]. This was accompanied by a reduction of the zeta potential [123], which would be coherent with a lower degree of dissociation [52]. As discussed previously, increasing the temperature will reduce the polyelectrolyte expansion of lignosulfonates, as a higher number of conformations become thermodynamically possible [116,118].…”
Section: Self-association and Agglomeration In Aqueous Solutionmentioning
confidence: 92%
See 1 more Smart Citation